Exflagellated Microgametes of Plasmodium Vivax in Human Peripheral Blood: An Uncommon Feature of Malaria - Prasad, C. S. B. R. (Springer-Verlag, 2011)
In the life cycle of malarial parasite exflagellation of microgametes occur in mosquitoes. Usually this will not occur in the peripheral blood of human beings. However, exflagellation can occur in the collected blood and may create diagnostic dilemma. We report a case of vivax malaria with exflagellated microgametes, which were mistaken for a double infection of vivax malaria and borrelia.